Emotional and Ecological Literacy for a More Sustainable Society - Panieri, Giuliana; Poto, Margherita Paola; Murray, Emily Margaret; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
This open access book aims to promote ecological and emotional research and education for sustainability by cultivating values and behaviours consistent with how nature makes us feel connected and nurtured. Built upon the intersection of ecological literacy and socio-emotional learning, grounded in sustainability and relational thinking, the research developed in the book covers a wide range of themes connected to the Agenda 2030. Giuliana Panieri is Professor at the Department of Geosciences at UiT The Arctic University of Norway Margherita Paola Poto is Research Professor at the Faculty of Law, UiT - The Arctic University of Norway and has taught Administrative Law for more than twenty years at the University of Turin, Italy. She is the project coordinator of ECO_CARE and the Ocean Incubator Network Emily Murray is a Ph.D. researcher in the School of Law, University College Cork, Ireland.
Introduction -- Chapter I: Achieving a Common Future for All Through Sustainability-Conscious Legal Education and Research Methods -- Chapter II: Methodological steps toward ecological and emotional education and research fostering multipotentiality -- Chapter III: Cross-disciplinary Methodology for Ocean Literacy: the example of the Ocean Senses Handbook -- Chapter IV: Wildlife/Ocean tourism: when emotions meet science -- Chapter V:Accessibility in Ocean Literacy/Marine Science/Ocean Conservation -- Chapter VI: The physical states of Water and their relationships: a dialogue between Brazil and Norway -- Conclusion.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: International relations; Environmental policy; International Relations Theory; Environmental Policy